Technique of Batch Adsorption for the Elimination of (Malachite Green) Dye from Industrial Waste Water by Exploitation Walnut Shells as Sorbent - Luma Ahmed Mohammed Ali; Ahmed Saleh Farhood; Firas Fadhel Ali (Universitas Gadjah Mada, 2017)
This study proposes an easy and cheap technique to get rid of dangerous Malachite Green (MG) dye from waste material by victimization carbon from walnut shells. The simple treatment was carried out by heating at temperature in which was set to the best carbonization degree to arrange carbon from these shells; thus, the temperature was set to 200 °C. Optimum conditions for sorption like the quantity of adsorbent, contact time, particle size of adsorbent, pH scale and initial MG concentration were conjointly examined. The results showed that the simplest removal was obtained once victimization 1 g of carbon with particle size 150 μM and time contact 150 min. However, the sorption of the dye was not affected by the pH except the sorption was very low at pH = 2. The removal potency was high approximating 99.53%. The results conjointly showed that the sorption equilibrium of MG onto carbon that was ready from the walnut shell has been evaluated via Langmuir and Freundlich models.